Konsep Pendidikan Akhlak Tasawuf Bagi Pendidikan Anak - Delfi Wulandari; Ismail Ismail; Alimni Alimni (UIN Fatmawati Sukarno Bengkulu, 2022)
The aim of this research is to determine the concept of Sufism moral education for children’s education. The research is library research using qualitative descriptive analysis methods. The aim of Sufism moral education is to appreciate the presence of God in life through appreciation of the beautiful names (qualities) of Allah (al-asma al-husna). With this appreciation, humans are expected to imitate God’s imitation morals, where God is the basis for moral nobility. In the end, human spirituality rises to the highest perfection, and becomes as close to God as human beings. The morals of Sufism as a process of Islamic education aim to ensure that humans practice noble ethics towards God, fellow humans and creatures in the universe. The attitude of ihsan is born from the practice of Sufi ethics. Therefore, the attitude of ihsan must be internalized in the Islamic education process. There is a need to internalize the value of ihsan as part of the Islamic education process. The attitude of ihsan is an attitude of progress in the stage of achieving closeness and love for Allah SWT.